In water or on land? A network meta-analysis of aquatic and land-based exercise interventions for pain and disability in chronic lower back pain - Wu, Hao; Diao, Penglin; Del Coso, Juan; Liu, Xiaoyu; Min, Yiwei; Ran, Ruimeng; Qiu, Bopeng; Zhang, Yinkai; Wang, Ziyu; Petersen, Carl (Frontiers in Medicine, 2026)
BackgroundChronic non-specific low back pain (CLBP) imposes a substantial healthcare burden. For CLBP, non-pharmacologic pain management within physical therapy/rehabilitation commonly relies on therapeutic exercise (exercise therapy). Aquatic interventions such as exercise and balneotherapy are widely prescribed to treat CLBP, but their comparative effectiveness against land-based exercise, and multi-model programs remain unclear. We performed a network meta-analysis of randomized controlled trials to compare the effects of aquatic, land-based exercise, and multi-modal interventions on pain and disability in patients with chronic low back pain.MethodsWe searched from inception to May 2025 for randomized controlled trials in adults with chronic non-specific low back pain that evaluated water-based therapies (aquatic exercise, hydrotherapy/balneotherapy). All randomized arms within eligible trials were retained, allowing comparisons with land-based exercise, combined aquatic + land-based programs, and general care/blank control.ResultsWe included 26 RCTs, forming a 9-node network (blank control, general care, land-based exercise, aquatic exercise, balneotherapy, and their combinations with general care/land-based exercise). For pain intensity, compared with blank control, balneotherapy + general care (SMD = 2.51, 95% CI 1.26–3.76; p < 0.001), aquatic exercise + general care (SMD = 1.96, 95% CI 0.44–3.48; p = 0.011), balneotherapy + land-based exercise (SMD = 1.68, 95% CI 0.58–2.78; p = 0.003), aquatic exercise (SMD = 1.58, 95% CI 0.83–2.32; p < 0.001), land-based exercise (SMD = 1.45, 95% CI 0.56–2.34; p = 0.001), and balneotherapy (SMD = 1.27, 95% CI 0.19–2.35; p = 0.021) significantly reduced pain. By contrast, land-based exercise + general care (SMD = 1.55, 95% CI − 0.18–3.27; p = 0.078) and general care (SMD = 1.02, 95% CI − 0.13–2.17; p = 0.081) did not reach statistical significance. Based on SUCRA for pain, balneotherapy + general care ranked first (SUCRA = 0.92; PrBest = 61.4%; mean rank = 1.7), followed by aquatic exercise + general care (0.71; 21.5%; 3.3) and balneotherapy + land-based exercise (0.62; 3.8%; 4.0), with combined interventions generally ranking above single modalities; blank control ranked last (0.01; 0.0%; 8.9). For clinical context, the observed SMDs correspond approximately to 24–48 points of pain reduction across the interventions that showed statistically significant effects. For disability, compared with blank control, balneotherapy + general care (SMD = 2.76, 95% CI 1.12–4.40; p = 0.001), balneotherapy (SMD = 2.48, 95% CI 0.50–4.45; p = 0.014), aquatic exercise + general care (SMD = 2.28, 95% CI 0.69–3.86; p = 0.005), balneotherapy + land-based exercise (SMD = 2.06, 95% CI 0.64–3.48; p = 0.004), aquatic exercise (SMD = 2.03, 95% CI 1.20–2.87; p < 0.001), land-based exercise (SMD = 1.84, 95% CI 0.80–2.88; p = 0.001), and general care (SMD = 1.66, 95% CI 0.11–3.21; p = 0.035) significantly reduced disability, whereas land-based exercise + general care did not (SMD = 1.72, 95% CI − 0.25–3.68; p = 0.086). SUCRA rankings for disability again favored multimodal care: balneotherapy + general care ranked first (SUCRA = 0.83; PrBest = 44.6%; mean rank = 2.4), followed by balneotherapy (0.71; 29.3%; 3.3) and aquatic exercise + general care (0.64; 16.9%; 3.9), with blank control consistently last (0.01; 0.0%; 8.9). Given very high heterogeneity and low-to-very-low certainty for most comparisons, these findings should be interpreted as preliminary directional evidence rather than actionable treatment recommendations. Results suggest multimodal approaches warrant investigation in future rigorously conducted trials.ConclusionIn CLBP, multimodal programs that integrate hydrotherapeutic components with general care or exercise tended to provide greater improvements than single interventions for both pain and disability. Among single modalities, effects were outcome-specific: for pain, aquatic exercise performed best and land-based exercise generally exceeded balneotherapy; for disability, balneotherapy and aquatic exercise showed larger improvements than land-based exercise. Land-based exercise remains a beneficial and pragmatic option where aquatic access is limited, while adding general care to land-based exercise did not show a consistent additional benefit. This analysis is substantially limited by very high heterogeneity (I2 > 85%) and predominantly very low certainty evidence. Of the 36 comparisons assessed for pain intensity, 94.4% (34/36) were rated low to very low certainty; for disability, all 36 comparisons were rated very low certainty. These evidence quality profiles severely restrict ranking reliability and recommendation strength.Systematic review registrationRegistered on PROSPERO. Unique Identifier: CRD42023432018. Public URL: https://www.crd.york.ac.uk/PROSPERO/view/CRD42023432018.